Investigating the Relation between Corporate Entrepreneurship And Employee Turnover Intention, Mediated by Job Satisfaction And Organizational Commitment: An Applied Study on Egyptian Petrochemicals Sector - Atta, Ossama; Metwally, Ayman; Ahmed, Maha Hafez; Ragheb, Mohammed A. (The Arab Journal of Administration, 2024)
This research is designed to investigate the effect of Corporate Entrepreneurship (CE) on Turnover Intention (TI) with mediation role of Job satisfaction (JS) and Organizational Commitment (OC): evidence from Egyptian Petrochemicals Sector. The objectives of This research are to investigate the relation among CE and TI, to test the relation among CE and JS, to test the relation among CE and OC, to explore the relation among JS and TI, to test the relation among OC and TI, to test the mediation role of JS among CE and TI. and to investigate the mediation role of OC among CE and TI. Using a questionnaire to collect data and AMOS software to conduct structural equation model (SEM) analyses, the methodology will be based on quantitative analysis. The primary findings of this paper are the direct effect among CE and TI is statistically significant, the direct effect among CE and JS is statistically significant, the direct effect among CE and OC is statistically significant, the direct effect among JS and TI is statistically significant, the direct effect among OC and TI is statistically significant, the study found that there is partial mediation effect of the OC among the relation of CE and TI in the Egyptian Petrochemicals Sector. Finally, the study found that there is partial mediation effect of the JS among the relation of CE and TI in the Egyptian Petrochemicals Sector.